Phases of Data Analysis - Glenn D. Israel (EDIS)
This document outlines the phases of data analysis for evaluating Extension programs, emphasizing the importance of tailoring the process to available resources and evaluation rigor. It covers steps such as screening data for errors, selecting key impact indicators, measuring and testing changes, comparing participant groups, and elaborating program impacts using statistical techniques. The goal is to enhance the credibility of findings and improve program effectiveness through rigorous analysis and collaboration among Extension professionals. Original publication date September 1992.